Power purchase agreements for risk and rent sharing in Himalayian hydropower developments - Glenn P. Jenkins; D. N. S. Dhakal (Queen's University, Department of Economics, 2008)
The Himalayan Rivers have an enormous hydropower potential that is still not exploited fully for the benefit of the region. Bhutan and Nepal together have an economically feasible potential of 60,000 MW of hydroelectric power generation capacity but are too weak financially to bear alone the risks associated with the development of their hydro resources. India is the only potential market for the electricity supplied from these sources. The power purchase agreement framework for the 336 MW Chukha Hydel Project in Bhutan could serve as a model with regards to the transfer of risks, management of risks, and sourcing of finance in exchange for the sharing of the economic rents associated with such projects. India undertook the costs and risks of constructing the hydroelectric dam and power plant in exchange for a reduced purchase price of electricity from the completed facility. This paper contains a financial and economic assessment of the Chukha Hydel Project. While India is in a position to exercise monopsonic power in this electricity market, this analysis shows that it is possible to have an agreement for sharing of the risks and returns between India and the Himalayan countries that is highly beneficial to all the stakeholders.
Keywords: H43; Q42; 330; hydropower; Himalayas; power purchase agreement; electricity; Bhutan; India; electricity exports; risk sharing; economic rents; Wasserkraftwerk; Finanzierung; Investitionsrisiko; Energiekonsum; Internationales Abkommen; Bhutan; Indien